Efficient cost-reducing preparation method of high-heat-resistance, high-conductivity and high-strength copper-chromium-niobium material
By using particle size partitioning and electrical pulse treatment methods in the preparation of copper chromium niobium materials, the problems of high preparation cost and low printing efficiency of copper chromium niobium materials are solved, and high-efficiency preparation of high-density materials is achieved and excellent machinery is achieved. Performance and conductivity.
Patent Information
- Application Number
- CN202411179930.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-27
AI Technical Summary
The existing copper chromium niobium materials have high cost, low printing efficiency, and difficult to form high density castings, and the preparation of diversified samples is difficult and costly.
The particle size of copper-chromium niobium alloy powder is 30-150μm. Through the steps of powder screening, preheating, electron beam printing and thermal compensation insulation, powder is spread in different regions and electrical pulse processing is carried out to optimize printing parameters to improve the flowability of the material. and density, reducing costs.
It has achieved efficient cost reduction and preparation of high heat resistance, high conductivity, high strength copper-chromium niobium materials, with tensile strength greater than 380MPa, hardness greater than 110HB, and conductivity greater than 47Ms/m. The process is simple, stable and easy to batch.
Smart Images

Figure CN119187600A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metal material manufacturing, and in particular to an efficient and cost-reducing preparation method of a high-heat-resistant, high-conductivity and high-strength copper-chromium-niobium material. Background Art
[0002] Copper-chromium-niobium material is a new material that is currently being widely promoted and tested in the aerospace industry. This material not only has a higher high-temperature conductivity than copper-chromium-zirconium (CuCr4Nb2 can reach a maximum conductivity of 48-50Ms / m after heat treatment at 850°C, and CuCr1Zr can reach a maximum conductivity of 43-45Ms / m after heat treatment at 530°C), but also has better high-temperature softening resistance, providing a solid material foundation for the development of aerospace. Parts produced by powder metallurgy (hot isostatic pressing / hot pressing sintering) of this material have been partially applied in the medical and electronic information fields. However, for aerospace, only the standard line of molten metallurgical parts can be used, which is a huge challenge for the current traditional smelting technology. The solubility and flow rate of the three phases of chromium-zirconium-copper are quite different, so castings cannot be formed. It is necessary to prepare the chromium-niobium alloy first and then add copper to melt it before preparing ingots or making powder. In order to promote the progress of the experiment, facilitate the modification of samples, shorten the production difficulty and cycle of mold manufacturing and machining, and increase the production efficiency of samples, the use of 3D printing has become an important research and development direction for this copper alloy material.
[0003] Patent CN110961628A discloses a 3D printing method for electron beam selective melting of high-density pure copper complex parts, which mainly uses the conventional printing method of electron beam to obtain pure copper high-density parts, avoiding the reflection and refractory problems during laser printing. However, this conventional printing process has very high requirements for raw materials, and the printing efficiency is also reduced due to the thin layer thickness, and the final cost is high and cannot be mass-produced.
[0004] Patent CN117655326A discloses a method for near-net-shape forming of the inner wall of a Cu-Cr-Nb combustion chamber by hot isostatic pressing. The method mainly prepares a near-net-shape combustion chamber blank by hot isostatic pressing and encapsulation, which reduces processing allowance and subsequent machining time and improves material utilization. However, for a variety of samples, the difficulty and cost of preparing the encapsulation are relatively high.
[0005] In order to solve the above problems, the present invention decides to solve the problems with a highly efficient and cost-reducing method for preparing a copper-chromium-niobium material with high heat resistance, high conductivity and high strength. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a highly efficient and cost-reducing method for preparing a copper-chromium-niobium material with high heat resistance, high conductivity and high strength.
[0007] A highly efficient and cost-reducing preparation method of a high-heat-resistant, high-conductivity, high-strength copper-chromium-niobium material comprises the following steps:
[0008] S1. Powder screening:
[0009] Copper-chromium-niobium alloy powder is selected as the raw material, and the particle size of the copper-chromium-niobium alloy powder is 30-150 μm, wherein D50=90 μm, D90=140 μm;
[0010] S2, preheating:
[0011] First, a Φ5x300 solid cylinder is printed at each of the four corners of the substrate as a preheating boundary, and the copper-chromium-niobium alloy powder is spread on the substrate to obtain a powder layer, and the powder layer is preheated as a solid support. The preheating temperature is 500-550° C., the scanning current is 1.0-4.5 mA, and the scanning speed is 4-9 m / s.
[0012] S3, electron beam printing:
[0013] The printing layer thickness is 0.05-0.08 mm, the number of layers is 2, and the vacuum degree is 2.5-3×10 -7 MPa;
[0014] The printing current is 3.5-8.5 mA, and the printing speed is 5-12 m / s.
[0015] The current for printing the outer contour is 0.8-1.5 mA, and the speed for printing the outer contour is 12-18 m / s;
[0016] After printing is completed, thermal compensation and heat preservation are performed to obtain copper-chromium-niobium material; the scanning current of the thermal compensation is 1.8-2.5 mA, the scanning speed of the thermal compensation is 9-15 m / s, and the heat preservation time of the thermal compensation is 3-6 hours.
[0017] Furthermore, in step S1, the copper-chromium-niobium alloy powder is any one of CuCr4Nb2 and CuCr8Nb4 prepared by gas atomization.
[0018] Description: The CuCrNb alloy powder can be made by gas atomization to solve the smelting problem of the insoluble metal niobium, and form a fine dispersed CrNb phase in the matrix, which improves the high temperature resistance and electrical conductivity after powder metallurgy. This is especially important for additive manufacturing technologies such as electron beam printing, and suitable alloy powder can ensure high printing efficiency and density of the finished product.
[0019] Furthermore, in step S2, the printing parameters of the solid cylinder adopt the same printing parameters as those in step S3.
[0020] Note: Uniform printing parameters can help reduce printing instability caused by parameter changes, thereby improving the repeatability of the printing process and the quality of the finished product. By maintaining consistent printing conditions, the heat management strategy can be simplified, and thermal stress and deformation caused by temperature differences can be reduced. Maintaining consistent printing parameters can help optimize the microstructure and properties of the material.
[0021] Furthermore, in step S2, the copper-chromium-niobium alloy powder is spread by:
[0022] The preheating area of the substrate is divided into an edge area, a transition area and a central area, wherein the transition area and the central area account for 70-80% of the preheating area, wherein the central area accounts for 50-60% of the preheating area, and the length-width ratio of the transition area and the central area is consistent with the length-width ratio of the preheating area, and the center points of the transition area and the central area coincide with the center point of the preheating area;
[0023] The copper-chromium-niobium alloy powder with a particle size of D50 is recorded as A powder, the copper-chromium-niobium alloy powder with a particle size of D90 and > D50 is recorded as B powder, and the copper-chromium-niobium alloy powder with a particle size > D90 is recorded as C powder;
[0024] Evenly mix 10-20% of A powder, 5-10% of B powder and 20-30% of C powder and spread them on the edge area.
[0025] Mix 5-10% of A powder, 15-20% of B powder and 30-40% of C powder evenly and spread them in the transition area.
[0026] The remaining A powder, B powder and C powder are evenly mixed and spread on the central area to obtain a powder layer.
[0027] Note: Dividing the powder layer into different areas and using powders with different particle size ratios can improve the fluidity of the material and the uniformity of powder spreading, avoid accumulation or gaps caused by poor powder fluidity, and ensure the geometric accuracy and surface quality of the formed parts; using a moderate powder particle size in the edge area is conducive to forming a more uniform thermal stress distribution during heating and cooling, and reducing material deformation caused by thermal expansion and contraction; larger powder particle size in the transition area can accelerate heat conduction and heat diffusion, help to quickly balance the temperature, and further reduce thermal stress; smaller powder particle size in the central area is conducive to more precise thermal control and optimization of the microstructure, and smaller powder particle size in the central area helps to improve the energy absorption efficiency of the laser or electron beam, reduce unfused powder, and improve the density and surface finish of the formed parts. Using larger powder particle size in the edge and transition areas can reduce the number of scans of the laser or electron beam and improve processing efficiency.
[0028] Furthermore, after the powdering is completed, the powder layer is subjected to electric pulse treatment, and the method of the electric pulse treatment is:
[0029] The edge area, transition area and central area are subjected to electric pulse treatment in turn, and the pulse frequency of the edge area is 150-300Hz, the pulse voltage is 25-35V, and the pulse treatment time is 50-150s; the pulse frequency and pulse voltage of the transition area are 1.3-1.5 times that of the edge area, and the pulse treatment time is 70-80% of that of the edge area; the pulse frequency and pulse voltage of the central area are 1.8-2 times that of the transition area, and the pulse treatment time is 1.3-1.5 times that of the transition area.
[0030] Explanation: The higher electric pulse frequency and voltage in the transition area help to heat quickly, promote material melting and optimize the microstructure, but the shorter time can reduce overheating and thermal stress accumulation and avoid material deformation. The lower frequency and voltage and longer processing time in the central area can achieve more uniform heating and melting, help control thermal stress and deformation, and promote microstructure refinement and performance improvement.
[0031] Compared with the existing copper-chromium-niobium material preparation method, the beneficial effects of the present invention are:
[0032] (1) The preparation method of the copper-chromium-niobium material of the present invention is developed on the basis of reducing costs, using powder with a larger particle size range to reduce raw material costs, using a higher layer thickness to reduce printing time costs, using thermal compensation scanning of the outer contour to optimize the surface of the part to reduce subsequent processing costs, and using thermal compensation insulation after printing to reduce the cost of subsequent re-furnace heat treatment. The tensile strength of the blank prepared by the present application is greater than 380Mpa, the hardness is greater than 110HB, and the conductivity is greater than 47Ms / m. The process is simple, stable, and easy to batch.
[0033] (2) When spreading powder, the present invention divides the powder layer into different areas and uses powders with different particle size ratios, which can improve the fluidity of the material and the uniformity of the powder spreading, avoid accumulation or gaps caused by poor powder fluidity, and ensure the geometric accuracy and surface quality of the formed part; using a moderate powder particle size in the edge area is helpful to form a more uniform thermal stress distribution during heating and cooling, and reduce material deformation caused by thermal expansion and contraction; the larger powder particle size in the transition area can accelerate heat conduction and heat diffusion, help to quickly balance the temperature, and further reduce thermal stress; the smaller powder particle size in the central area is conducive to more precise thermal control and optimization of the microstructure, and the smaller powder particle size in the central area helps to improve the energy absorption efficiency of the laser or electron beam, reduce unfused powder, and improve the density and surface finish of the formed part, while using a larger powder particle size in the edge and transition areas can reduce the number of scans of the laser or electron beam and improve processing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a metallographic diagram of the copper-chromium-niobium material of Example 1 in the method for preparing the copper-chromium-niobium material of the present invention observed under an electron microscope at 200X;
[0035] Figure 2 This is a metallographic diagram of the copper-chromium-niobium material of Example 1 in the method for preparing the copper-chromium-niobium material of the present invention observed under an electron microscope at 1000X;
[0036] Figure 3 This is the powder distribution diagram of Example 13 in the preparation method of the copper-chromium-niobium material of the present invention. DETAILED DESCRIPTION
[0037] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0038] Example 1: A highly efficient and cost-reducing preparation method of a high heat-resistant, high-conductivity, high-strength copper-chromium-niobium material, comprising the following steps:
[0039] S1. Powder screening:
[0040] Copper-chromium-niobium alloy powder is selected as the raw material, the particle size of the copper-chromium-niobium alloy powder is 40-145 μm, wherein D50=90 μm, D90=140 μm; the copper-chromium-niobium alloy powder is commercially available CuCr4Nb2 prepared by gas atomization;
[0041] S2, preheating:
[0042] First, a solid cylinder of Φ5x300 is printed at each of the four corners of the substrate as a preheating boundary. The printing parameters of the solid cylinder are the same as those in step S3. The copper-chromium-niobium alloy powder is spread on the substrate to obtain a powder layer. The powder spreading method is to evenly mix the copper-chromium-niobium alloy powder and then evenly distribute it on the substrate. The powder layer is preheated as a solid support. The preheating temperature is 525° C., the scanning current is 2 mA, and the scanning speed is 6.5 m / s.
[0043] S3, electron beam printing:
[0044] The printing layer thickness is 0.06mm, the number of printing layers for the entity and the outer contour is 2 layers, and the vacuum degree is 2.8×10 -7 MPa;
[0045] The printing current is 6.5mA and the printing speed is 8m / s.
[0046] The current for printing the outer contour is 1.2mA, and the speed for printing the outer contour is 15m / s;
[0047] After printing is completed, thermal compensation and heat preservation are performed to obtain copper-chromium-niobium material; the scanning current of the thermal compensation is 2.2 mA, the scanning speed of the thermal compensation is 12 m / s, and the heat preservation time of the thermal compensation is 4.5 h;
[0048] pass Figure 1 and Figure 2 It can be seen that the prepared copper-chromium-niobium material has fine grains and uniform structure.
[0049] Example 2: This example is different from Example 1 in that the particle size of the copper-chromium-niobium alloy powder is 30-145 μm, wherein D50=90 μm, D90=140 μm; the copper-chromium-niobium alloy powder is commercially available CuCr4Nb2 prepared by gas atomization.
[0050] Example 3: This example is different from Example 1 in that the particle size of the copper-chromium-niobium alloy powder is 40-150 μm, wherein D50=90 μm, D90=140 μm; the copper-chromium-niobium alloy powder is commercially available CuCr8Nb4 prepared by gas atomization.
[0051] Example 4: This example is different from Example 1 in that the preheating temperature is 500° C., the scanning current is 1.0 mA, and the scanning speed is 4 m / s.
[0052] Example 5: This example is different from Example 1 in that the preheating temperature is 550° C., the scanning current is 4.5 mA, and the scanning speed is 9 m / s.
[0053] Example 6: This example is different from Example 1 in that the printing layer thickness is 0.05 mm, the number of printing layers of the entity and the outer contour is 2 layers, and the vacuum degree is 2.5×10 -7 MPa.
[0054] Example 7: This example is different from Example 1 in that the printing layer thickness is 0.08 mm, the number of printing layers of the entity and the outer contour is 2 layers, and the vacuum degree is 3×10 -7 MPa.
[0055] Embodiment 8: This embodiment differs from Embodiment 1 in that the printing entity current is 3.5 mA and the printing entity speed is 5 m / s.
[0056] Embodiment 9: This embodiment differs from Embodiment 1 in that the printing entity current is 8.5 mA and the printing entity speed is 12 m / s.
[0057] Example 10: The difference between this example and Example 1 is that the current for printing the outer contour is 0.8 mA and the speed for printing the outer contour is 12 m / s.
[0058] Example 11: The difference between this example and Example 1 is that the current for printing the outer contour is 1.5 mA and the speed for printing the outer contour is 18 m / s.
[0059] Example 12: This example is different from Example 1 in that the scanning current of the thermal compensation is 1.8 mA, the scanning speed of the thermal compensation is 9 m / s, and the holding time of the thermal compensation is 3 h.
[0060] Example 13: This example is different from Example 1 in that the scanning current of the thermal compensation is 2.5 mA, the scanning speed of the thermal compensation is 15 m / s, and the holding time of the thermal compensation is 6 h.
[0061] Embodiment 14: This embodiment differs from Embodiment 1 in that, in step S2, the copper-chromium-niobium alloy powder is spread by:
[0062] like Figure 3 As shown, the preheating area of the substrate is divided into an edge area, a transition area and a central area, the transition area and the central area account for 75% of the preheating area, wherein the central area accounts for 55% of the preheating area, the length-to-width ratio of the transition area and the central area is consistent with the length-to-width ratio of the preheating area, and the center points of the transition area and the central area coincide with the center point of the preheating area;
[0063] The copper-chromium-niobium alloy powder with a particle size of D50 is recorded as A powder, the copper-chromium-niobium alloy powder with a particle size of D90 and > D50 is recorded as B powder, and the copper-chromium-niobium alloy powder with a particle size > D90 is recorded as C powder;
[0064] Mix 15% of A powder, 7% of B powder and 25% of C powder evenly and spread them on the edge area.
[0065] Mix 7% of A powder, 18% of B powder and 35% of C powder evenly and spread them in the transition area.
[0066] The remaining A powder, B powder and C powder are evenly mixed and spread on the central area to obtain a powder layer.
[0067] Embodiment 15: This embodiment differs from Embodiment 14 in that the transition area and the central area account for 70% of the preheating area, wherein the central area accounts for 60% of the preheating area.
[0068] Embodiment 16: This embodiment differs from Embodiment 14 in that the transition area and the central area occupy 80% of the preheating area, wherein the central area occupies 50% of the preheating area.
[0069] Example 17: This example is different from Example 14 in that 10% of A powder, 5% of B powder and 30% of C powder are evenly mixed and spread on the edge area.
[0070] Example 18: This example is different from Example 14 in that 20% of A powder, 10% of B powder and 20% of C powder are evenly mixed and spread on the edge area.
[0071] Example 19: This example is different from Example 14 in that 5% of A powder, 15% of B powder and 40% of C powder are evenly mixed and spread on the transition area.
[0072] Example 20: This example is different from Example 14 in that 10% of A powder, 20% of B powder and 30% of C powder are evenly mixed and spread on the transition area.
[0073] Example 21: This example is different from Example 14 in that after the powder is spread, the powder layer is subjected to electric pulse treatment, and the method of the electric pulse treatment is:
[0074] The edge area, transition area, and center area were subjected to electric pulse treatment in turn, and the pulse frequency of the edge area was 225 Hz, the pulse voltage was 30 V, and the pulse treatment time was 100 s; the pulse frequency and pulse voltage of the transition area were 1.4 times that of the edge area, and the pulse treatment time was 75% of that of the edge area; the pulse frequency and pulse voltage of the center area were 1.9 times that of the transition area, and the pulse treatment time was 1.4 times that of the transition area.
[0075] Example 22: This example differs from Example 21 in that the pulse frequency of the edge area is 150 Hz, the pulse voltage is 25 V, and the pulse processing time is 50 s.
[0076] Example 23: This example differs from Example 21 in that the pulse frequency of the edge area is 300 Hz, the pulse voltage is 35 V, and the pulse processing time is 150 s.
[0077] Example 24: This example differs from Example 21 in that the pulse frequency and pulse voltage in the transition region are 1.3 times those in the edge region, and the pulse processing time is 70% of that in the edge region.
[0078] Example 25: This example differs from Example 21 in that the pulse frequency and pulse voltage in the transition region are 1.5 times that in the edge region, and the pulse processing time is 80% of that in the edge region.
[0079] Example 26: This example differs from Example 21 in that the pulse frequency and pulse voltage in the central region are 1.8 times that in the transition region, and the pulse processing time is 1.3 times that in the transition region.
[0080] Example 27: This example differs from Example 21 in that the pulse frequency and pulse voltage in the central region are twice that in the transition region, and the pulse processing time is 1.5 times that in the transition region.
[0081] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0082] For the copper-chromium-niobium materials prepared in each embodiment, the tensile strength and electrical conductivity were tested respectively, and the average value of the experimental values of five tests each time was taken as the final result. The specific research is as follows:
[0083] 1. Investigate the effects of powder particle size and preheating parameters on the tensile strength and conductivity of copper-chromium-niobium materials.
[0084] Table 1 Tensile strength and conductivity of copper-chromium-niobium materials in Examples 1 to 5
[0085]
[0086]
[0087] It can be seen from the results in Table 1 that if the copper-chromium-niobium alloy powder particle size is too large and the preheating parameters are too small or too large, the tensile strength and electrical conductivity of the copper-chromium-niobium material will be reduced. In Example 2, the copper-chromium-niobium material has a smaller particle size, so that the tensile strength of the material is higher than that of Example 1, but the electrical conductivity is reduced. Therefore, in a comprehensive comparison, the parameter effect of Example 1 is relatively better.
[0088] 2. Investigate the influence of printing parameters on the tensile strength and conductivity of copper-chromium-niobium materials.
[0089] Table 2 Tensile strength and conductivity of copper-chromium-niobium materials in Examples 6 to 13
[0090]
[0091] It can be seen from the results in Table 2 that too small or too large printing layer thickness and vacuum degree, too small or too large printing entity parameters, too small or too large printing outer contour parameters, and too small or too large thermal compensation parameters will reduce the tensile strength and conductivity of the copper-chromium-niobium material. The particle size of the copper-chromium-niobium material in Example 2 is smaller, so that the tensile strength of the material is higher than that in Example 1, but the conductivity is reduced. Therefore, in comprehensive comparison, the parameter effect of Example 1 is relatively better.
[0092] 3. Investigate the effect of powder spreading method before preheating on the tensile strength and conductivity of copper-chromium-niobium materials.
[0093] Table 3 Tensile strength and conductivity of copper-chromium-niobium materials in Examples 14 to 20
[0094]
[0095] From the results in Table 3, it can be seen that Examples 14 to 20 have improved the powder spreading method, thereby significantly improving the performance of the copper-chromium-niobium material compared to Examples 1 to 13;
[0096] Furthermore, analysis of Examples 14 to 20 shows that too small or too large a proportion of the central region, too small or too large a proportion of C powder in the edge region, and too small or too large a proportion of C powder in the transition region will reduce the tensile strength and conductivity of the copper-chromium-niobium material. Therefore, in comprehensive comparison, the parameter effect of Example 14 is relatively better.
[0097] 4. Investigate the effect of electric pulse treatment before preheating on the tensile strength and conductivity of copper-chromium-niobium materials.
[0098] Table 4 Tensile strength and conductivity of copper-chromium-niobium materials in Examples 21-27 and Comparative Examples 1-3
[0099]
[0100]
[0101] The difference between Control Example 1 and Example 21 is that the electric pulse parameters of each region are the same;
[0102] The difference between Comparative Example 2 and Example 21 is that the pulse frequency and pulse voltage in the transition region are lower than those in the edge region;
[0103] The difference between Comparative Example 3 and Example 21 is that the pulse frequency and pulse voltage in the central region are lower than those in the transition region;
[0104] From the results in Table 4, it can be seen that, based on the exploration 3, Examples 21-27 further perform regional targeted electric pulse treatment on the powder layer, and the tensile strength and conductivity of the copper-chromium-niobium material are improved to a certain extent compared with Examples 14-20; Control Example 1 lacks regional targeted electric pulse treatment, and the electric pulse treatment rules of the transition area and the central area in Control Examples 2 and 3 are opposite to those in Example 21, so the tensile strength and conductivity of the copper-chromium-niobium material are reduced compared with Examples 21-27;
[0105] By comparing Examples 21 to 27, it can be seen that if the camouflage parameters of the edge area are too small or too large, the relationship multiples between the transition area and the edge area are too small or too large, and the relationship multiples between the center area and the transition area are too small or too large, they will all reduce the improvement in the tensile strength and conductivity of the copper-chromium-niobium material. Therefore, in comprehensive comparison, the parameter effect of Example 21 is relatively better.
Claims
1. An efficient and cost-reducing preparation method of a high heat-resistant, high-conductivity, high-strength copper-chromium-niobium material, characterized in that: The following steps are involved: S1. Powder screening: Copper-chromium-niobium alloy powder is selected as the raw material, and the particle size of the copper-chromium-niobium alloy powder is 30-150 μm, wherein D50=90 μm, D90=140 μm; S2, preheating: First, a Φ5x300 solid cylinder is printed at each of the four corners of the substrate as a preheating boundary, and the copper-chromium-niobium alloy powder is spread on the substrate to obtain a powder layer, and the powder layer is preheated as a solid support. The preheating temperature is 500-550° C., the scanning current is 1.0-4.5 mA, and the scanning speed is 4-9 m / s. S3, electron beam printing: The printing layer thickness is 0.05-0.08 mm, the number of printing layers for the entity and the outer contour is 2 layers, and the vacuum degree is 2.5-3×10 - 7 MPa; The printing current is 3.5-8.5 mA, and the printing speed is 5-12 m / s. The current for printing the outer contour is 0.8-1.5 mA, and the speed for printing the outer contour is 12-18 m / s; After printing is completed, thermal compensation and heat preservation are performed to obtain copper-chromium-niobium material; the scanning current of the thermal compensation is 1.8-2.5 mA, the scanning speed of the thermal compensation is 9-15 m / s, and the heat preservation time of the thermal compensation is 3-6 hours.
2. The method for efficiently reducing costs of preparing a high heat-resistant, high-conductivity, high-strength copper-chromium-niobium material according to claim 1, characterized in that: In step S1, the copper-chromium-niobium alloy powder is any one of CuCr4Nb2 and CuCr8Nb4 prepared by gas atomization.
3. The high-efficiency and cost-reducing preparation method of a high-heat-resistant, high-conductivity, high-strength copper-chromium-niobium material according to claim 1 is characterized in that: In step S2, the printing parameters of the solid cylinder adopt the same printing parameters as those in step S3.
4. The method for efficiently reducing costs of preparing a high heat-resistant, high-conductivity, high-strength copper-chromium-niobium material according to claim 1, characterized in that: In step S2, the copper-chromium-niobium alloy powder is spread by: The preheating area of the substrate is divided into an edge area, a transition area and a central area, wherein the transition area and the central area account for 70-80% of the preheating area, wherein the central area accounts for 50-60% of the preheating area, and the length-width ratio of the transition area and the central area is consistent with the length-width ratio of the preheating area, and the center points of the transition area and the central area coincide with the center point of the preheating area; The copper-chromium-niobium alloy powder with a particle size of D50 is recorded as A powder, the copper-chromium-niobium alloy powder with a particle size of D90 and > D50 is recorded as B powder, and the copper-chromium-niobium alloy powder with a particle size > D90 is recorded as C powder; Evenly mix 10-20% of A powder, 5-10% of B powder and 20-30% of C powder and spread them on the edge area. Evenly mix 5-10% of A powder, 15-20% of B powder and 30-40% of C powder and spread them in the transition area. Evenly mix the remaining A powder, B powder and C powder and spread them in the center area. The powder spreading is completed to obtain a powder layer.
5. The method for efficiently reducing costs of preparing a high heat-resistant, high-conductivity, high-strength copper-chromium-niobium material according to claim 4, characterized in that: After the powdering is completed, the powder layer is subjected to electric pulse treatment, and the method of the electric pulse treatment is as follows: The edge area, transition area and central area are subjected to electric pulse treatment in turn, and the pulse frequency of the edge area is 150-300Hz, the pulse voltage is 25-35V, and the pulse treatment time is 50-150s; the pulse frequency and pulse voltage of the transition area are 1.3-1.5 times that of the edge area, and the pulse treatment time is 70-80% of that of the edge area; the pulse frequency and pulse voltage of the central area are 1.8-2 times that of the transition area, and the pulse treatment time is 1.3-1.5 times that of the transition area.
Citation Information
Cited By
Method for preparing copper-chromium-niobium alloy high-thermal-conductivity component based on green laser SLM
CN120190361A